2020
DOI: 10.3390/en13174365
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Electric Vehicle Demand Response Programs in a Grid with Varying Levels of Renewable Energy Sources: Time-of-Use Tariff versus Smart Charging

Abstract: An increase in variable renewable energy sources and soaring electricity demand at peak hours undermines the efficiency and reliability of the power supply. Conventional supply-side solutions, such as additional gas turbine plants and energy storage systems, can help mitigate these problems; however, they are not cost-effective. This study highlights the potential value of electric vehicle demand response programs by analyzing three separate scenarios: electric vehicle charging based on a time-of-use tariff, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…(2) and (3), as well as its addresses with instrumental variables, and treatment by means of a two-stage estimation approach (Jeon et al, 2020).…”
Section: Analytical Methodologymentioning
confidence: 99%
“…(2) and (3), as well as its addresses with instrumental variables, and treatment by means of a two-stage estimation approach (Jeon et al, 2020).…”
Section: Analytical Methodologymentioning
confidence: 99%
“…In terms of EV potential for demand management, Nazaripouya, Wang [81] examined the role of EV as a mobile and flexible energy storage system that brings new opportunities in terms of tariff and solving future tariff challenges. Jeon, Cho [90] analysed the potential value of EV demand response programs for Korea through scenario analysis. Across all scenarios it was found that there were enough benefits from demand response and EV to attract the customers, with "smart control" V2G capability delivering the largest reduction in costs.…”
Section: Relationship Between Tariff Structure and Demand Managementmentioning
confidence: 99%
“…The use of EVs in a VPP has been very popular recently. In [10], the use of electric vehicle demand response to reduce operating costs and improve the reliability of the power system with a large share of variable renewable sources and electric vehicles is shown. The study was based on the example of Jeju Island, located in South Korea.…”
Section: Power Quality Electric Vehicles and Economymentioning
confidence: 99%